As’taka Raya pavilion / Wan Nur Tasnim Taram Satiraksa ... [et al.] - Taram Satiraksa, Wan Nur Tasnim; Mohd Padli, Nurul Hizzati; Nazri, Nur Ain Sofia (2024)
As’taka Raya is timber-based inspired by Malaysia’s national flower known as Hibiscus or Bunga Raya. Raya in Malaysia can also be interpreted as celebration. As a multiracial country that consists of Malay, Indian and Chinese which contributes to many celebrations such as Eid-Al Fitr, Deepavali and Chinese New Year. Despite the differences, Malaysian people find a way to create unity among themselves. Hence, the idea of As’taka Raya was created to enhance the unity and creating an easy space without any boundaries between the Malaysia’s students. This space can be used as a place for gathering and bonding to encourage students to gain more social skills. This space also provides a relaxing area for those who want to seek serenity and tranquility. As’taka Raya offers a couple of activities for students such as gardening, discussing, working, and recreational activities.